EFEKTIVITAS KINERJA PENYULUH PADA KELOMPOK PENGOLAH AMPLANG DI KELURAHAN SANGA-SANGA DALAM KECAMATAN SANGA-SANGA - Pangesti Putri Ekasari; Bambang Indratno Gunawan; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
The purpose of this study was to determine the effectiveness of the performance of fisheries instructors in Sanga-Sanga Dalam Village in the fishery product processing group. This research was carried out in April 2019 - February 2020 in Sanga-Sanga Kelurahan in Sanga-Sanga District. The sampling method used is the Survey method with the number of samples taken is 15 people. Data analysis method used is descriptive qualitative analysis method. The results of the research The effectiveness of instructors' performance in the amplang processing group in Sanga-Sanga in Sanga-Sanga District based on 8 indicators on the performance of instructors, namely Work Quantity with a value of 6, Work Quality with a value of 5, work knowledge with a value of 8.33, creativity with value 6.87, cooperation with a value of 7.07, can be trusted with a value of 6.73, initiative with a value of 7.93, and personal quality with a value of 8.06. Cumulatively, the average is in the medium category with a total score of 55.99. Keywords: Effectiveness, Extension Workers, Amplang Processing Group.